2008
DOI: 10.1016/j.ijsu.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Intra-peritoneal duodenal perforation caused by delayed migration of endobiliary stent: a case report

Abstract: Endoscopic biliary stenting is an accepted modality of palliation of malignant biliary obstructions. Delayed stent migration causing intra-peritoneal perforation of duodenum, is a rare life threatening complication. Proximal adhesion of stent to the tumor is believed to increase the intensity of distal trauma produced by the intra-duodenal segment, preventing its adaptation to intestinal peristalsis and causing perforation. Low bacterial load and containment of leak by gut and omentum blunts the clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Notably, patients can present with nonspecific symptoms; therefore, a high index of suspicion for perforation should be maintained when evaluating these patients, irrespective of the duration of the stent placement [3,4]. Our two cases demonstrate that duodenal perforation can occur in both benign and malignant settings, regardless of the type of stent or its length of time in place.…”
Section: Cases and Techniques Library (Ctl) E281mentioning
confidence: 78%
“…Notably, patients can present with nonspecific symptoms; therefore, a high index of suspicion for perforation should be maintained when evaluating these patients, irrespective of the duration of the stent placement [3,4]. Our two cases demonstrate that duodenal perforation can occur in both benign and malignant settings, regardless of the type of stent or its length of time in place.…”
Section: Cases and Techniques Library (Ctl) E281mentioning
confidence: 78%
“…The rate of duodenal injury in cases with distal migration was relatively high in the present study (up to 36%). However, only limited case reports reported distal migration-induced duodenal perforation thus far [6,7,17,[22][23][24]; hence, the risk factors of duodenal injury due to distal migrated stents remain uncertain. Sanchez-Tembleque et al [17] suggested that the inflexibility of the stent may influence migration and related duodenal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for distal stent migration include benign strictures and ampullary stenosis [10]. The most likely site for perforation is in the duodenum or bowel containing herniae [3,14].…”
Section: Discussionmentioning
confidence: 99%